Football - Bloody Hell! : The Biography of Alex Ferguson - Barclay, Patrick (London Yellow Jersey Press, 2010)
Alex Ferguson is the most fascinating and controversial figure in football today. He is also the most successful. His twenty five year tenure of the Manchester United dugout has seen him win everything there is to be won in football, many times over. His reign as manager has led to the rise of Manchester United to become the biggest football club in the world. This book, written by the award-winning and critically.
Include Illustrations, Bibliography and Index.
The Biography of Alex Ferguson.
Keywords: Soccer managers -- Scotland -- England--Manchester